Effectiveness and cost-effectiveness of a virtual multidisciplinary stroke care clinic for community-dwelling stroke survivors and caregivers: a randomised controlled trial protocol. Issue 5 (10th May 2019) - Chau, Janita Pak Chun; Lo, Suzanne Hoi Shan; Lee, Vivian Wing Yan; Choi, Kai Chow; Shum, Edward Wai Ching; Hung, Zevari Sheung Sheung; Mok, Vincent Chung Tong; Siow, Elaine Kee Chen; Ching, Jessica Yuet Ling; Lam, Simon Kwun Yu; Yeung, Jonas Hon Ming; Li, Siu Hung; et al.
Abstract : Introduction: The virtual multidisciplinary stroke care clinic (VMSCC) is the first nurse-led clinic developed to offer support to community-dwelling stroke survivors and caregivers, and to promote poststroke recovery. This two-arm randomised controlled trial will evaluate its effectiveness on survivors' self-efficacy (SE), survivors' and caregivers' health-related quality of life (HRQoL) and cost-effectiveness on emergency admissions and length of readmission hospital stay. Methods and analysis: A consecutive sample of 384 stroke survivor–caregiver dyads will be recruited from four hospitals. An online platform that embraces readily accessible and reliable information will be developed. Participants randomly assigned to the intervention group will receive usual care plus the VMSCC service. The service includes access to a tablet containing 30 videos demonstrating appropriate self-care strategies, communication with a registered nurse monthly through video and telephone calls and regular blood pressure monitoring. Primary outcomes include survivors' SE in self-management and survivors' and caregivers' HRQoL. Secondary outcomes include survivors' performance of self-management behaviours, depression and social participation; and caregivers' coping strategies, satisfaction with caring and depression. Data will be collected at baseline, and at 3 and 6 months after commencing the intervention. Survivors' and caregivers' satisfaction with the service will be assessed at 6-month follow-up. Multivariable regressions and generalised estimating equations model will be conducted. Survivors' emergency admissions and length of hospital stay will be evaluated during the 6-month follow-up period. Cost-effectiveness analysis will be performed on the average total cost incurred. Discussion: The results will inform stakeholders about incorporating the VMSCC service into current stroke rehabilitation service. Ethics and dissemination: This protocol was approved by the Joint Chinese University of Hong Kong-New Territories East Cluster Clinical Research Ethics Committee (CREC Ref. No.: 2017.660). All participants will provide written informed consent. Results will be disseminated through scientific publications, and presentations at local and international conferences. Trial registration number: ChiCTR1800016101; Pre-results.